Numerical study on the nanofluid flows and temperature behaviors in the spirally coiled tubes with helical ribs. (October 2021) - Naphon, P.; Wiriyasart, S.; Prurapark, R.; Srichat, A.
Abstract: The nanofluids heat transfer and flow behaviors in the spirally coiled tube with and without helical ribs are simulated using the Eulerian two-phase turbulent model. A model used in the present study is 8.5 mm diameter copper tube, bending into the spirally coiled tube with and without helical ribs under constant wall temperature conditions. As flowing in the spirally coiled tube, the secondary flow is induced by the centrifugal force. In contrast, the swirling flow is caused by the pipe's helical ribs, which have significant effects on the Brownian motion of nanoparticles suspending the base fluid and then results in higher heat transfer enhancement. It can be found that the helical rib configurations have a significant effect on the velocity and temperature contours. The Nusselt number from the spirally coiled tube with helical ribs is 12.45% higher than those without helical ribs. However, due to more flow complexity and roughness augmentation, the pressure drop across the test section also increases. Besides, adding 0.05% nanoparticles by volume to water enhances the Nusselt number by 8.21%—also, the overall enhancement in heat transfer.